Calls of the wild? 'Fake' sound effects and cinematic realism in BBC David Attenborough nature documentaries. Issue 1 (1st April 2017) - Collins, Karen
The BBC's Planet Earth II represented a landmark in natural history documentary television, using the latest technologies to capture nature in ways never before seen or heard. But the series was mired in accusations of 'fakery' and 'trickery' when it came to the sound, due to its entirely post-production soundtrack. This article explores these accusations in the context of the history of Attenborough documentaries and contemporary practice.